PENGARUH PEMBERIAN INSENTIF TERHADAP KINERJA KARYAWAN PADA PT. BANK TABUNGAN PENSIUN NASIONAL Tbk. BANDAR JAYA TAHUN 2015 - Savitri, Citra (LPPM STKIP PGRI Bandar Lampung, 2015)
This research aims to identify and analyze the performance of employees of PT.Bank Tabungan Pensiun Nasional. Tbk Cab. Bandar Jaya. Relation to the mattershow employees can work as well as possible and employees have a high motivation to finish the job with the incentives. Than, this studyaims to show the significance of the effect of incentives on employee performance.In analyzing the data the author uses descriptive analysis that shows the distribution of items of each variable, then the analysisis done by taking the results of the study and then entered into the statistical formula: Ttest or Thit and hypothesis testing. From the results of the questionnaire (questionnaire) distributed to employees of PT.Bank BTPN Cab. Bandar Jaya know that the independent variable (X) incentives with the item bonuses, commissions, and profit share significan and positive impact on the performance of employees partially in SMO and SMS PT Bank BTPN Cab. Bandar Jaya